BRAIN GYM DAN PENGUIN DANCE MAMPU MENINGKATKAN KECERDASAN EMOSIONAL ANAK - Ribkha Itha Idhayanti; Riski Novita Sari; Bambang Sarwono (Politeknik Kesehatan Kementrian Kesehatan Semarang, 2022)
Emotional intelligence is the ability to process, recognizing, control emotions, motivate oneself, and build relationships. The level of emotional intelligence in RA Darusallam Muaradua is still low around 26 (30%) children. In Indonesia, an outline home health survey data analysis (SKRT, 2012) regarding the emotional symptoms of mental disorders of children aged 5-14 years is 114 per 1000 children. The impact of low children emotional intelligence, children often appear to be fussy, tend to have difficulty exspressing their annoyances and their anger appropriately, stubborn and difficult to socialize. Physical activities used to improve children's emotional intelligence are brain gym and penguin dance.The purpose of this study was to determine the increase in children's emotional intelligence through brain gym and penguin dance techniques in preschool children. The type of research is quantitative, quasi-experimental research method with a research design of Two Group Pre-test and Post-test with control group design. The population in this study is preschool in 2020 RA with a total of 65 children. The sampling technique in this study uses non-probability (purposive sampling) to obtain a sample of 36 children. The observation sheet used to assess the level of emotional intelligence of children is the UNIT GSS-EAS.Data analysis was carried out with the Wilcoxon test showing that the value of p = 0.000 0.05, it can be concluded that Ha is accepted. This means that there is an increase in children's emotional intelligence before and after the brain gym and penguin dance techniques are carried out. The results of the Mann Whitney test showed p = 0.004 0.05, the group after being given the Brain Gym and Penguin Dance techniques, had a mean rank value of the Brain Gym technique of 23.53, while the Penguin Dance technique was 13.47, so it can be seen the mean rank the Brain Gym technique is greater than the Penguin Dance technique, which means that the Brain Gym technique is equally effective in increasing the emotional intelligence of preschool children